Cognitive bias modification of interpretation in children with social anxiety disorder. (January 2017) - Orchard, Faith; Apetroaia, Adela; Clarke, Kiri; Creswell, Cathy
Highlights: Children with social anxiety disorder were assigned to CBM-I training or no training. We measured the effects on interpretation bias and social anxiety. CBM-I was not associated with greater change in interpretations than no training. Social anxiety symptoms and diagnoses were not influenced by CBM-I training. More intensive CBM-I training may be required. Abstract: Negative (or a lack of positive) interpretation of ambiguous social situations has been hypothesised to maintain social anxiety disorder in children, yet there is currently limited evidence to support this. Cognitive Bias Modification of Interpretation (CBM-I) provides a means to explore the causal influence of interpretation bias on social anxiety disorder, and has been associated with a reduction in social anxiety symptoms in adults. Seven to twelve year old children with a diagnosis of social anxiety disorder completed CBM-I training, adapted from materials designed for socially anxious children in the community, or no training. Effects on interpretation bias and social anxiety were assessed. The adapted CBM-I training was not associated with significant changes in benign or negative interpretation. Unsurprisingly given the lack of successful interpretation training, there were no significant changes in child or parent reported social anxiety symptoms, clinician-rated severity or diagnoses and change in interpretation was not significantly associated with change in social anxiety. These findings contrast with some studies with community populations although it is possible that more intensive CBM-I training is required to fully test this hypothesis among clinical groups.